Public perceptions of non-pharmaceutical interventions for influenza and mosquito-borne illnesses – a statewide survey in Arizona. (July 2020) - Pogreba-Brown, K; Austhof, E; Okello, A; Weiss, J; Lira, R; Ernst, K
Aims: We conducted a statewide online survey to understand public knowledge, attitudes, and practices (KAP) related to non-pharmaceutical interventions (NPIs) for mosquito-borne diseases and influenza in Arizona. Methods: The survey included knowledge of diseases, major health concerns, and sources of health information and KAP of NPIs for influenza and mosquito-borne diseases. Our team worked with Qualtrics ®, an online survey company, to recruit a representative sample of 1500 adults in Arizona. Results: Of the 1531 respondents who completed the survey, most indicated that chronic conditions were their primary health concern (48%), with the other half split between infectious diseases (25%) and health effects of environmental conditions (26%). The majority (88%) of respondents indicated that they use the Internet to get their health information. Approximately one in eight people reported not emptying standing water and reducing potential mosquito habitats, despite respondents citing them as being the most effective factors in reducing mosquitoes. Regarding specific diseases, about half of the respondents were concerned about West Nile virus and/or Zika virus. Most (85%) people knew the signs and symptoms of influenza and 63% of people reported being likely to get the influenza shot. Those who did not vaccinate ( n = 285) reported concerns that the vaccine would make them sick (41%), was ineffective (37%), or others indicated, 'I don't want to' (37%). Conclusions: Overall, respondents were most concerned with chronic conditions and received their information from the Internet. Knowledge about mosquito-borne diseases was low. There were high levels of acceptance and self-reported uptake of the influenza vaccine.